Pengembangan Materi Ajar Mata Kuliah Pembelajaran Basa Jawa Berbasis Translation Bahasa Indonesia (Studi di Prodi PGMI STAI Al-Hikmah Tuban) - Ahmad Suyanto (LPPM Institut Agama Islam Al-Hikmah Tuban, 2021)
Lectures are a very pleasant thing for some active students. For passive students, lectures are a scourge themselves. For example he does not like one of the courses, so he will rarely enter. This greatly disrupts the learning climate in the classroom. The Center HotelOn the campus of the Al Hikmah Islamic School of Tuban one of them is a number of courses that are disliked by students, especially PGMI students. The course is Javanese Language Learning in MI / SD. This subject is very disliked by most students, because one of the reasons they do not understand the meaning of the Javanese language. The Javanese say,